Recidivism and Desistance in Young Offenders: Criminal Trajectory Analysis from Self-Reported Offenses, Substance Use and Professional Judgment - Pérez-Luco, Ricardo (Pontificia Universidad Javeriana, 2012)
We analyzed responses of 239 male adolescents convicted of various crimes and offenses, grouped into six trajectories defined psychological characteristics, risks and problem behavior. The self-reporting of crimes is obtained with the “EDA” scale, problematic abuse with the “DEP-ADO” grid, risks and resources with “IRNC” inventory and the “FERR” grid, from official crime the court records. The purpose was to characterize differentially criminal trajectories, retrospectively, analyzing the relationship between self-reported crime volume, substance abuse, accumulation of risk factors and resources and penalties. The results show different trends for trajectories with diverse potential recidivism and desistance, independent of the penalty executed. We discuss basing the need for differentiated intervention programs criminal trajectories.